An unsuitable job for a woman - James, P. D. (London : Faber and faber, 2010)
Cordelia Gray, head of Pryde's Detective Agency, finds herself embroiled in a murder mystery when she sets out to investigate the apparent suicide of a young Cambridge student.
Young Adult.
Young Adult
Keywords: Gray, Cordelia (Fictitious character) -- Fiction; Women private investigators -- England -- Fiction; Gray, Cordelia (Fictional character) -- Fiction; Mystery fiction; Women private investigators -- Fiction; Mystery fiction